\(e^+e^−\) \(→\) hh AND \(e^+e^−\) \(→\) ɸh COLLISION IN THE RANDALL-SUNDRUM MODEL - Thi Ha Giang, Bui; Thi Le Thuy, Dao (HNUE Journal of Science: Journal of Natural Sciences, 2016)
Although the Standard Model (SM) describes successfully almost all existing experimental data, the model suffers from many theoretical drawbacks. Some models have been suggested that involve extra dimensions. One models which can solve the hierarchy problem is the Randall-Sundrum model (RSM). The RSM involves two three-branes bounding a slice of 5D compact anti-de Sitter. Gravity is localized in the hidden brane while the SM fields are supposed to be localized in the visible brane. The fluctuations for the size of the extra dimension are characterized by the scalar component of a matric called the radion (ɸ). The phenomenological similarity and the mixing potential of the radion and the Higgs boson warrant detailling to distinguish them at colliders. We study e+e−\(→\)hh and e+e− \(→\) ɸh collisions in RSM.